Hubungan Antara Pendidikan Karakter dan Hasil Belajar Matematika Siswa SMA - Zebua, Amin Kristin; Mendrofa, Netti Kariani; Harefa, Amin Otoni; Telaumbanua, Yakin Niat (Program Studi Pendidikan Matematika, 2024)
This research was motivated by students' low mathematics learning outcomes at one of the State High Schools in Umbunasi. The primary purpose of this study is to analyze the relationship between character education and mathematics learning outcomes. This study uses a quantitative approach with an associative descriptive method emphasizing the cause-and-effect relationship. The research design applied is correlational. The research subjects comprised 24 students in grade XII-Science at the State High School. The instruments used to collect data include observations, questionnaires, tests, interviews, and documentation. The study results showed that the questionnaire and test data were normally distributed. The hypothesis test using the t-test produced a local value = 603, more significant than the ttable value = 1.717, which means that the null hypothesis (H0) was rejected, indicating a significant relationship between character education and mathematics learning outcomes. The results of the product-moment correlation test showed a calculation value = 0.700, more significant than the table = 0.404, which showed a strong relationship between the two variables and the contribution of character education of 49.06% to mathematics learning outcomes.